Remarkably Few Sputum Cultures from People with Parkinson’s Disease during Hospital In-Patient Admission - Richard W. Walker; Joel English; Grace Tan; Annette Fisher; William K. Gray (Parkinson's Disease)
Although respiratory tract infections can be a common complication in people with Parkinson’s disease (PD), there is little published data on the nature of such infections in this patient group. We wished to investigate whether sputum samples were being taken from PD patients in order to establish whether an infection was present and if so which bacteria were responsible for the infection. We recorded the number of positive sputum samples taken from admission to North Tyneside General Hospital in North-East England across a ten-year period from June 2001 to June 2011. Of 643 in-patient episodes involving people with PD, positive sputum samples were recorded for only 12 episodes (1.9%) in eight patients. All patients were in early stage disease. In all admissions to the NHS Trust running the hospital, there were 23,069 sputum cultures from 1,056,693 in-patient episodes (2.2%). Our findings may reflect the difficultly of expectorating in many people with PD, particularly in late-stage disease. Since people with PD are especially vulnerable to respiratory tract infections, clinicians need to ensure that, where possible, a sputum sample is obtained from people with PD when clinically indicated.